(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
HaroldBloom in his book Genius: A Mosaic of One Hundred Exemplary CreativeMinds (2002) embarks on juxtaposing one hundred geniuses of languageaccording to the Sefirot. Kabbalah as a body of speculation relies upon ahighly figurative language. "Chief among its figurations or metaphors isthe Sefirot, attributes at once of God and of the Adam Kadmon or Divine Man,God’s Image,"